Features of the physicaland psycho-emotional state of men in the first period ofadulthood in conditions - Mamedov , Z. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. In recent years, the health of the adult population of Ukraine has deteriorated, with an increase in cases of hypertension, angina pectoris, and myocardial infarction. According to scientific data, about 70% of adults have a low or below average level of health. Today, the situation is complicated by the armed conflict in the country, which has led to the spread of signs of emotional distress among the population and has negatively affected their health. Under such conditions, it is advisable to study the indicators of the physical and psycho-emotional state of mature people to identify existing deficiencies and their timely correction by means of health-improving and recreational physical activity. The purpose of the study – to investigate the indicators of the physical and psychoemotional state of men in the first period of adulthood in order to determine the means of their correction in the system of recreational and health-improving activities. Materials and methods: analysis of literary sources, questionnaires, anthropometric research methods, methods for determining functional status, determining the level of physical condition according to the O. A. Pirogova index, personal and situational anxiety according to the Spvlberger-Khanin method. Results.Analysis of the survey results shows that about 36.6% of respondents regularly engage in physical culture in their free time. Among all types of physical activity, martial arts are currently the most popular among men (chosen by 66.6% of respondents). Astudy of the physical development of men in the first period of adulthood shows that 23.3% of them were overweight. Heart rate and blood pressure were at the upper limit of normal. The results of functional tests with breath holding did not reach age norms. The orthostatic test results showed a lack of fitness in the subjects. The subjects had a high level of personal and situational anxiety according to the Spielberger-Khanin scale. Conclusions. There is a need to improve the indicators of the physical and psycho-emotional state of men in the first period of adulthood by involving them in regular recreational and health-improving activities.